The Assessment of the Bioeconomy and Biomass Sectors in Central and Eastern European Countries - Ionela Mițuko Vlad (Agronomy, 2022)
Since the enlargement of the European Union, the CEE (Central and Eastern European) countries have brought a larger share of agricultural and forest land with high potential for biomass and bioenergy. The progress of bioeconomy is intercorrelated with the dimension of agriculture, which is the major provider of biomass for food and feed and for other bio-based industries. This research aims to assess the dimension of agriculture-based and food-based bioeconomy, with focus on the production and use of biomass. Conducted over the 2008–2019 period with data from the EU and OECD, the study pointed out the role of CEE countries in the European bioeconomy. Thus, we estimated that the bioeconomy market reached, in 2019, a turnover of almost EUR 324 billion (around 14% of the EU level), respectively, EUR 79 billion from agriculture-based sectors and EUR 116.8 billion from food-based sectors. The number of employees has decreased; in 2019, in bioeconomy sectors were employed 6.9 million people (almost 40% of the EU bioeconomy employment). Regarding the production of biomass, the study has revealed an increase of the share in EU production from 25.7% in 2008 to 27.8% in 2019, due to a growth of biomass by 7.1%. With this study, we emphasize the need to support more sustainable demand of biomass and to make the bioeconomy market more competitive. In addition, we point out several problems of the bioeconomy sector, such as insufficient data, low productivity, and the unused or underused sources of biomass.